Performance evaluation and exergy analysis of a novel combined cooling, heating and power (CCHP) system based on liquid air energy storage. (1st May 2021) - Xue, Xiao-Dai; Zhang, Tong; Zhang, Xue-Lin; Ma, Lin-Rui; He, Ya-Ling; Li, Ming-Jia; Mei, Sheng-Wei
Abstract: Liquid air energy storage (LAES) is a promising large-scale energy storage technology in improving renewable energy systems and grid load shifting. In baseline LAES (B-LAES), the compression heat harvested in the charging process is stored and utilized in the discharging process to enhance the power generation. Due to the low liquid air yield, a large amount of compression heat is wasted. In order to improve the round-trip efficiency (RTE) and extend the application field, a novel combined cooling, heating and power system based on the LAES (LAES-CCHP) is proposed and investigated. In the proposed system, an organic Rankine cycle (ORC) is employed to recover the high-temperature surplus compression heat to generate electricity and an absorption refrigeration system (ARS) is introduced to utilize the low-temperature compression heat to realize district cooling and heating. Based on a mathematical model, performance evaluation and exergy analysis of the system is performed. It is found that the effective and cascaded utilization of the compression heat could significantly improve the efficiency and performance of the system. With optimal operational parameters, the RTE and exergy efficiency of the LAES-CCHP could reach 69.64% and 57.02%, respectively, which are 37.66% and 12.71% higher than those of the B-LAES. Highlights: A novel CCHP system based on liquid air energy storage is proposed and studied. The ORC and absorption refrigeration cycle are employed in the proposed system. The compression heat is effective and cascaded utilized to realize trigeneration. Energy and exergy analysis of the system and each component were conducted. The round-trip efficiency of the proposed system could reach to 69.24%.